New tungstate fluorophosphate glasses - Poirier, G.; Poulain, M.; Messaddeq, Younes [UNESP]; Ribeiro, SJL (Elsevier B.V., 2005)
\A new class of tungstate fluorophosphate glasses was identified in the NaPO3-BaF2-WO3 ternary system. The variation of several physical properties was determined with respect to chemical composition. Characteristic temperatures, density and refractive index increase as tungsten oxide content increases. The optical transmission range and specially the energy bandgap depend of the WO3 amount. No crystallization could be observed for the Most WO3 concentrated vitreous samples (greater than or equal to20% molar). Color and optical properties of the glasses depend of the melting time because of the presence of reduced tungsten species like W5+ and W4+. In addition, photodarkening is observed in tungsten rich glass samples under UV laser illumination and this phenomenon can be reversible by heat treatment near the glass transition temperature. (C) 2004 Published by Elsevier B.V.